Behavior of human periodontal ligament cells on dentin surfaces ablated with an ultra-short pulsed laser. Issue 1 (December 2017) - Liu, Jing; Andrukhov, Oleh; Laky, Markus; Nürnberger, Sylvia; Moritz, Andreas; Lyu, Peijun; Rausch-Fan, Xiaohui
Abstract This study aimed to evaluate the effects of an ultrashort pulsed laser (USPL) (1064 nm, 20 ps, 100 kHz) with different laser fluences (F, 4, 6, 8 J/cm2 ) and pulse overlaps (PO, 0, 50%) on human periodontal ligament cells (hPDLs) behavior. Dentin samples were ablated with USPL with different combinations of fluences and pulse overlaps; some samples were ablated with an Er:YAG laser (2940 nm, 150 µs, 100 mJ/pulse, 5 J/cm2 ) and some samples were ground with a carbide bur. Then hPDLs were grown on the samples after different treatments. Dentin morphology and cell adhesion were observed with SEM and gene expressions were measured by RT-PCR. The results showed dentin surfaces ablated with USPL when F = 4 J/cm2, PO = 0, and F = 6 J/cm2, PO = 0 were partially intact with obvious ridges and valleys and cells on these surfaces grew mostly along the valleys. USPL ablated surfaces in other groups were entirely ablated and cell cluster formation was observed. The RT-PCR results showed an upregulation of osteocalcin of cells grown on the dentin after some laser treatment. It can be concluded that USPL could improve the attachment and differentiation of hPDLs and thus potentially promote periodontal tissue regeneration.